KNOWLEDGE MANAGEMENT SYSTEM UNTUK MENDUKUNG PENGETAHUAN ANTAR PERAWAT STUDI KASUS RUMAH SAKIT UMUM KOTA TANGERANG SELATAN - Lukman Nulhakim (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2016)
General Hospital of South Tangerang City (RSU) has a main focus is public health services in the surrounding area. To improve services, RSU always follow the development of science in the field of health, especially on the part of nurses. The development of science is very important to the hospital, because with such knowledge will help the hospital to handle new cases developing in society. To handle these issues are the researchers create a draft design of nursing knowledge management. The purpose of this study is to provide convenience in managing knowledge that is in the general hospital of South Tangerang city, especially the knowledge of nurses and to create a culture of learning in the hospital environment through the exchange of knowledge, such as the sharing of knowledge among nurses, communication forums nurses as container create a culture of learning for nurses so it is easy to learn and provides the solution of the problems being encountered. The methodology used in this studyrefers to the Inukshuk knowledge management methodology developed by Kimiz Dalkir and methods of the four phase of the 10-step KM roadmap developed by Amrit Tiwana with some adjustments by the researcher. The tools used in designing knowlede Management This is bydesign approach and object-oriented analysis or Object Oriented Analysis and Design (OOAD) using notation Unified Modeling Language (UML). Results of design knowledge management is expected to provide an overview solution to the problem of limited space and time to exchange knowledge. In addition design nursing knowledge management can give you a documentation of knowledge by utilizing information technology. Design Knowledge Management of nursing that was only a prototype and needed further development to perfection Knowledge Managemet nursing.